The Influence of Self-Determination on Non-suicidal Self-harm (NSSH) Sufferers in Yogyakarta Students - Syafii, Muhammad Hisyam; Gusti, Icha Liara (Journal of Islamic Communication and Counseling, 2025)
This study aims to investigate the relationship between the concept of Self-Determination Theory (SDT) and self-harm behavior among students in Yogyakarta. Using a quantitative approach, the analysis used is simple linear regression analysis, with the subjects of this research being 84 student respondents in Yogyakarta. The sampling technique used by researchers is purposive sampling. The instruments used by researchers are the self-determination theory approach and the Self-Harm Inventory (SHI) instrument which aims to assess self-harm behavior. This instrument consists of 22 items and the relative autonomy index (RAI), namely a score that predicts an individual's level of autonomy, which consists of 94. The research results show a strong relationship. The R-squared value shows the percentage of variability in y that is explained by x. The R-squared is 0.85, which means that 85% of the variability in y is explained by x. Apart from that, in the results there is a significant (p<0.5) influence that self-determination has an influence on self-harm behavior.